Measuring the Spatial Configuration of the Center Point of Indonesia Using Space Syntax - Andi Andre Pratama Putra,; Djubir R. E. Kembuan,; Desty Rara Retna Kalude,; Heince Andre Maahury, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study aims to analyse the spatial configuration caused by the development and urbanisation that occurred in Makassar, especially in the Center Point of Indonesia area. The method used in the study uses a space syntax approach that provides graphic analysis results that show the relationship between the built environment and human activities in space. The city spatial plan map in the Center Point of Indonesia by 2030 area was analysed using Depthmap X. The syntactic measure used is integration and choice, both globally (Rn) and locally (R3). The results of the analysis conducted show that the Center Point of Indonesia area itself does not have a high value of integration and choice both globally and locally, but the roads that connect the area, namely Metro Tanjung Bunga Road and Cenderawasih Road, are the most integrated roads.